Cover Image, Volume 7, Issue 2. Issue 2 (27th February 2019) - Li, Pao; Xie, Jing; Tang, Hui; Shi, Cong; Xie, Yanhua; He, Jing; Zeng, Yulun; Zhou, Hongli; Xia, Bo; Zhang, Chunyan; Jiang, Liwen
Abstract : The cover image is based on the Original Research Fingerprints of volatile flavor compounds from southern stinky tofu brine with headspace solid‐phase microextraction/gas chromatography–mass spectrometry and chemometric methods by Pao Li et al., DOI: 10.1002/fsn3.943 .